Soil habitat condition shapes Tamarix chinensis community diversity in the coastal saline-alkali soils - Yu, Qianjun; Suo, Lizhu; Qi, Ji; Wang, Yi; Hu, Qiuli; Shan, Yan; Zhao, Ying (Frontiers in Plant Science, 2023)
Unfavorable coastal saline-alkali soil habitats degrade plant community diversity and reduce terrestrial ecological functions. Previous studies have been conducted on the mechanisms by which certain saline-alkali soil properties determine plant community diversity, however, how those properties synergistically affect plant community diversity remains unclear. Here, 36 plots of typical Tamarix chinensis communities were investigated for a range of parameters at three different distances (10, 20, and 40 km) from the coastline in the Yellow River Delta between 2020 and 2022, and corresponding soil samples were taken and analyzed. Our results suggest that although T. chinensis density, ground diameter, and canopy coverage significantly increased (P<0.05) with increasing distance from the coast, the communities with the most plant species were found at 10 to 20 km distance from the coastline, indicating the effects of soil habitat on T. chinensis community diversity. Simpson dominance (species dominance), Margalef (species richness), and Pielou indices (species evenness) differed significantly among the three distances (P<0.05) and were significantly correlated with soil sand content, mean soil moisture, and electrical conductivity (P<0.05), indicating that soil texture, water, and salinity were the main factors governing T. chinensis community diversity. Principal component analysis (PCA) was performed to construct an integrated soil habitat index (SHI) representing the synthesis of the soil texture-water-salinity condition. The estimated SHI quantified a 64.2% variation in the synthetic soil texture-water-salinity condition and was significantly higher at the 10 km distance than at the 40 and 20 km distances. The SHI linearly predicted T. chinensis community diversity (R2 = 0.12–0.17, P<0.05), suggesting that greater SHI (coarser soil texture, wetter soil moisture regime, and higher soil salinity) was found closer to the coast and coincided with higher species dominance and evenness and lower species richness in the T. chinensis community. These findings on the relationship between T. chinensis communities and soil habitat conditions will be valuable in planning the restoration and protection of the ecological functions of T. chinensis shrubs in the Yellow River Delta.